2013
DOI: 10.1039/c3sm27786k
|View full text |Cite
|
Sign up to set email alerts
|

A multi-cellular network of metabolically active E. coli as a weak gel of living Janus particles

Abstract: A multi-cellular network of metabolically active E. coli as a weak gel of living Janus particles Remigijus Šimkus, * a Romas Baronas b and Žilvinas Ledas b Bioluminescence images of nutrient rich liquid cultures of lux-gene reporter Escherichia coli were recorded for several hours after being placed into small diameter cylindrical containers (glass tubes and microtiter plate wells). It was found that luminous cells distribute near the three-phase contact line forming an irregular array of clumps, channels and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 47 publications
7
30
0
Order By: Relevance
“…It has been recently shown that bioluminescence imaging can be employed to validate mathematical models of bacterial self‐organization. In particular, the abovementioned merging–emerging patterns were, to the best of our knowledge, for the first time observed experimentally in cylindrical samples of liquid cultures of bioluminescent Escherichia coli . The imagining showed luminous aggregates of bacteria merging and emerging along the three‐phase contact lines.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…It has been recently shown that bioluminescence imaging can be employed to validate mathematical models of bacterial self‐organization. In particular, the abovementioned merging–emerging patterns were, to the best of our knowledge, for the first time observed experimentally in cylindrical samples of liquid cultures of bioluminescent Escherichia coli . The imagining showed luminous aggregates of bacteria merging and emerging along the three‐phase contact lines.…”
Section: Introductionmentioning
confidence: 55%
“…This is in line with the predictions of the KSF model. However, patterns of self‐organization are best captured with unexpected values of cell growth rate and diffusivity of chemoattractant . In an attempt to explain this, a phenomenological model of metabolic self‐organization was suggested in a paper by Šimkus and Baronas .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diameter of the bacterium is d = 1 m, while the density is i = 1.415 g/cm 3 , [13]. The density of the glass surface is j = 2.470 g/cm 3 . During the interaction of the bacterium and the glass surface, the bacterium is surrounded by water.…”
Section: Basic Data Of Simulationmentioning
confidence: 99%
“…Different approaches can be applied for the simulation of bacteria motion. The diffusion and chemotaxis of bacterial cells are processes playing a fundamental role for active suspension behaviour and biofilm formation [3]. Using particle interpretation for a description of bacterium interaction, the Discrete Element Method (DEM) can be taken into account.…”
Section: Introductionmentioning
confidence: 99%